2013
DOI: 10.1111/jnc.12615
|View full text |Cite
|
Sign up to set email alerts
|

The role of NMDA and mGluR5 receptors in calcium mobilization and neurotoxicity of homocysteine in trigeminal and cortical neurons and glial cells

Abstract: Recent studies suggested contribution of homocysteine (HCY) to neurodegenerative disorders and migraine. However, HCY effect in the nociceptive system is essentially unknown. To explore the mechanism of HCY action, we studied short-and long-term effects of this amino acid on rat peripheral and central neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
57
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 74 publications
(184 reference statements)
0
57
0
Order By: Relevance
“…With live imaging, we also compared the ability of these compounds to generate Ca 2+ transients in trigeminal neurons and satellite glial cells and to evaluate the action of CGRP on the functional activity of ATP and its dephosphorylated metabolites. As these cultures contained both neurons and glial cells [38], we distinguished neurons from glial cell by the high responsiveness of the former to K + (notice last application in the trace in Fig. 7a).…”
Section: Nucleotide Ca 2+ Signaling In Trigeminal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…With live imaging, we also compared the ability of these compounds to generate Ca 2+ transients in trigeminal neurons and satellite glial cells and to evaluate the action of CGRP on the functional activity of ATP and its dephosphorylated metabolites. As these cultures contained both neurons and glial cells [38], we distinguished neurons from glial cell by the high responsiveness of the former to K + (notice last application in the trace in Fig. 7a).…”
Section: Nucleotide Ca 2+ Signaling In Trigeminal Cellsmentioning
confidence: 99%
“…Therefore, next, we performed measurements of ATP, ADP, AMP, and adenosine in trigeminal ganglion cultures. Notably, trigeminal cultures consist of both neurons and several types of satellite cells, which are likely contributors to migraine pain [27,38].…”
Section: Basal Level Of Nucleotides In Trigeminal Cells and Effect Ofmentioning
confidence: 99%
“…Hyperhomocysteinemia might contribute to elevate intracellular Ca 2? levels through NMDA and mGluR5 receptors [40]. It can also trigger endothelial dysfunction and pro-coagulation through the involvement of oxidative stress [41].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine (Hcy) is an amino acid and several observational studies have shown that Hcy is a risk factor for cardiovascular disease and idiopathic pain, like migraine [32]. Recently, glutamatergic sensitization of trigeminal neurons and satellite glial cells (SGC) by Hcy through NMDA and mGluR5 receptors with a selectivity of effect according to the considered cell has been demonstrated [32].…”
Section: Homocysteinementioning
confidence: 99%
“…Recently, glutamatergic sensitization of trigeminal neurons and satellite glial cells (SGC) by Hcy through NMDA and mGluR5 receptors with a selectivity of effect according to the considered cell has been demonstrated [32]. Furthermore, Hcy leads to production of metabolites (homocysteic acid and cysteine sulfinic acid), acting as NMDA receptors with neurotoxic effects on dopaminergic neurons [33].…”
Section: Homocysteinementioning
confidence: 99%